Tragédia no palco : o casamento em Bodas de sangre, de García Lorca, e Vestido de noiva, de Nelson Rodrigues - Oliveira, Rociele de Lócio (2015)
The research analyses, on a comparative approach, the wedding representation in the theatre plays Vestido de noiva (1943) by Nelson Rodrigues and Bodas de Sangre (1933) by Federico Garcia Lorca aiming at verifying the treatment given by the dramatists to love triangles, announced during the protagonists wedding ceremony. Nelson Rodrigues depicts a Brazilian scenario in which is displayed a conflict lived by middle-class bourgeoisie women in an urbanized modern society. Garcia Lorca’s play represents the muzzled feelings of Spanish women in their affective relations taking place in a rural and conservative space. The two oeuvre have passion and transgression of moral, religions and legal imposition as sources of all conflicts, that will result in the death of its main characters. The two World Wars and the Spanish Civil War mark the time of personal tragedies in the playwriting of both authors.